Modernism and Postmodernism. The Margins of Articulation - Rainer Nägele (Studies in 20th & 21st Century Literature, 1980)
The difference between 'Modernism' and 'Postmodernism' is not one of definitions. The latter is rather a radicalization of a tendency inherent already in Modernism: calling into question the underlying principles of definitions, delimitations and boundaries. If, in Modernism, this tendency is marked by an increasing self-reflective gesture of the text, Postmodernism radicalizes this self-reflection to the point where the self-reflective circle and its closure are broken. The subversion of demarcation takes place not only on the semantic level, but on the level of the text's literal and linguistic qualities. Such a move displaces particularly any totalizing project, which, for example, is implied in Jürgen Habermas's recent critique of Post-modernism. The following essay traces some of these effects in the development of the German novel of the last two decades and in some examples of experimental and concrete texts, where the reflection on the principle of demarcation leads to the margins of articulation and with that to the margin where the cultural opposition of culture/nature is constituted.
Keywords: Modernism; Postmodernism; self-reflective; self-reflection; demarcation; Jürgen Habermas; German novel; culture; nature